Cricetid rodents from the Rancho El Ocote fauna, late Hemphillian (Pliocene), Guanajuato - Oscar Carranza-Castañeda; Anne H. Walton (Revista Mexicana de Ciencias Geológicas)
The rodent assemblage of the late Hemphillian  El Ocote local in central Mexico resembles that of the Yepómera fauna of northern Mexico, but the El Ocote fauna lacks such northern genera as Copemys… in order to continue, download the full paper in PDF.